VNIISSOK'S VEGETABLES FOR THE SPACE EXPLORATION - V.F. Pivovarov; A.P. Primak; M.I. Fedorova; M.M. Tareeva (Овощи России)
Now the 2011 is a Year of Russian Cosmonautic as it was announced according to the edict of President of Russia Federation. The 50 years from the first human's flight into the space is being marked this year. On 12 April, 1961, for the first time in human's history the Soviet citizen Yuri Gagarin was a first man to perform a flight into the space on board of Vostok spaceship. Having flown around the planet he successfully landed. It was a 108 minutes' flight, only one circle which became the greatest event not only for 20b century but also for history of civilization. All-Russian Research Institute of Vegetable Breeding and Seed Production as some other Research Institutes of RAAS have been now working out the foodstuffs for cosmonauts since the time when Russian Space Exploration Program began.